Depression Phenotype, Inflammation, and the Brain: Implications for Future Research. Issue 4 (May 2016) - Krishnadas, Rajeev; Harrison, Neil A.
Abstract : ABSTRACT: Inflammation is implicated in the etiology of major depressive disorder (MDD). Human neuroimaging techniques are increasingly used to characterize the neural circuitry mediating actions of inflammation on mood, motivation, and cognition and its relationship to MDD. In this issue of Psychosomatic Medicine, Byrne and colleagues report the first systematic review of these studies. The systematic review provides a much-needed synthesis of current research findings and highlights the role of cortical and subcortical brain structure and function. In this accompanying commentary, we highlight further points of particular relevance to future studies, including the potential advantages of functional phenotype models rather than the emphasis on mutually exclusive diagnostic categories in describing MDD and other psychiatric disorders. Novel imaging techniques will further enhance possibilities to clarify the link between inflammation and depression. New research challenges are described regarding the relationships between behavioral phenotype, brain structure and function, and peripheral inflammation.